Impact of socio-economic factors on marital instability among market women in Ibadan South-West Local Government (2014)
Marriage institution has witnessed a lot of problems in the recent times which in turn affect the stability of marriage. Market Women especially are witnessing a lot of crises in their marriage due to several factors. But economic factor is the tree that produced or abhor other factors. There have been a lot of controversies as to what extent can economic factors really affect the stability of marriage. It is against this background that this study looked at the impact of socio-economic factors on marital (in) stability among market women. The survey research design was adopted for this study. The population for this study consists of market women in Oja Oba and Alesinloye market in Ibadan South-West Local Government in Oyo State, a total of three hundred women were randomly selected for this study. The main instrument for the study was the Socio-Economic Factors and Marital Stability Questionnaire [SEFMSQ]. The findings of this study revealed that the impact of occupation, religion, education, sex and daily income on marital stability was significant, but the most potent factors was daily income (Beta = 0.739 P<0.05) followed by occupation (Beta = 0.130, P <0.05) and sex (Beta = 0.007, P< 0.05). The table reveals that religion and level of education are not potent predictors of martial stability. It shows that income, occupation and sex are predictable factors to marital stability in this study. Based on the finding of this research work the government should make policies that will create job opportunities for her citizenry. There should be government and non-governmental support for couple(s) who lost their jobs. The policy of retrenchment of workers should be jettisoned, social workers and community workers should go all opt and bring to the understanding of the public, especially the markct women about this issue that is affecting the marital stability which is a very vital institution Also based on these findings it is recommended that youth who intent to many should seek the informed counsel of a professional marriage counselor to help them in making the right choices and exposing them to the indices of economic compatibility in marriage.